Changes in the Oral Health-Related Quality of Life in Infants With Cleft Lip and/or Palate Before and After Surgical Treatment - Lopez Ramos, Roxana Patricia (2021)
The author(s) disclosed receipt of the following financial support for the research, authorship, and/or publication of this article: The principal author Lopez Ramos, Roxana Patricia is a doctoral student studying an Epidemiological Research Doctorate at Universidad Peruana Cayetano Heredia under FONDECYT/CIENCIAACTIVA scholarship EF033-235-2015 and supported by training Grant D43 TW007393 awarded by the Fogarty International Center of the US National Institutes of Health.